Efek Ekstrak Etanol Daun Mobe (Artocarpus lacucha Buch-Ham.) terhadap Histopatologi Hati Tikus Diinduksi Karbon Tetraklorida - Lubis, Meiva Amelia; Dalimunthe , Aminah; Sitorus , Panal; Satria , Denny; Pertiwi , Indah; Damayanti S , Damayanti S (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Liver injury due to exposure to hepatotoxic chemicals remains a major problem in the medical and pharmaceutical fields. Carbon tetrachloride (CCl₄) is a classic hepatotoxic agent that induces oxidative stress, lipid peroxidation, and hepatocyte necrosis through free radical formation. Mobe leaves (Artocarpus lacucha Buch-Ham.) contain bioactive compounds, particularly flavonoids and phenolics, which possess antioxidant and anti-inflammatory properties with potential hepatoprotective effects. Objective: This study aimed to evaluate the effect of ethanol extract of mobe leaves (EEML) on the liver histopathology of rats induced with carbon tetrachloride. Methods: This experimental study used a post-test only control group design. Twenty-five male rats were divided into five groups: negative control (CMC-Na 1% + CCl₄), positive control (silymarin 100 mg/kgBW + CCl₄), and three treatment groups receiving EEML at doses of 50, 100, and 200 mg/kgBW + CCl₄. Hepatotoxicity was induced by intraperitoneal injection of CCl₄ (1 mL/kgBW) twice weekly for 14 days. Liver tissue was processed for hematoxylin-eosin staining, and histopathological changes (hepatocyte degeneration, necrosis, and inflammatory cell infiltration) were assessed semi-quantitatively using a scoring system (0-3). Results: CCl₄ induction caused severe liver damage in the negative control group, characterized by diffuse hydropic degeneration, extensive necrosis, and marked inflammatory infiltration (score 3 for all parameters). EEML administration significantly reduced liver injury in a dose-dependent manner. The 200 mg/kgBW dose showed the most pronounced hepatoprotective effect, with degeneration score 2, necrosis score 1, and inflammation score 2, approaching the protective effect of silymarin (score 1 for all parameters). Conclusion: Ethanol extract of mobe leaves demonstrated hepatoprotective activity against CCl₄-induced liver damage in rats, with the optimal effect at 200 mg/kgBW. These findings support the potential of mobe leaves as a natural hepatoprotective agent.